2017
DOI: 10.3233/cbm-170601
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapy-associated hemoglobin on prognosis of colorectal cancer patients receiving adjuvant chemotherapy

Abstract: Chemotherapy-associated hemoglobin < 90 g/L has a significant prognostic value in CRC receiving adjuvant chemotherapy, which is a significant biomarker in the individualized management and may suggest the simple indication for the treatment of anemia in adjuvant chemotherapy in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Wei et al . ( 14 ) showed that the baseline platelet count correlated with recurrence in 286 patients with stage II-III CRC receiving adjuvant chemotherapy. The optimal cut-off affecting recurrence was 276×10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al . ( 14 ) showed that the baseline platelet count correlated with recurrence in 286 patients with stage II-III CRC receiving adjuvant chemotherapy. The optimal cut-off affecting recurrence was 276×10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells, the most important oxygen-carrying medium in the body, will induce hypoxia or a hypoxic microenvironment when they differ in size or their functions are impaired. This microenvironment may accelerate the formation of tumor neovascularization by stimulating the production of vascular endothelial growth factor (VEGF) in the body [27]. Hypoxia or a hypoxic microenvironment can also induce the expression of the hypoxia-inducible factor (HIF) family, which may lead to tumor progression, cancer aggravation or poor prognosis [28].…”
Section: Plos Onementioning
confidence: 99%
“…Wei also reported that Hb changes after adjuvant chemotherapy is related to the prognosis of CRC patients [17]. The point is stage II and III patients are all confounded in that study and receive FOLFOX regimen treatment, while IDEAL study suggests only stage II CRC patients with high risks are recommended to be adjuvantly treated.…”
Section: Discussionmentioning
confidence: 90%
“…Yang [5] found that red blood cell distribution width was closely related to colorectal cancer metastasis. Wei [6] reported that chemotherapy-associated hemoglobin might be a prognostic bio-marker. Zhang [7] claimed that elevated red blood cell volume distribution width-the change of diversity (RDW-CV) might be an independent predictive factor in resectable rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%